Outer Baduy as an Eco-Gastronomic Tourism Destination Area (Outer Baduy Eco-Gastronomic Study) - Pambudi, Bondan; Gunawijaya, Jajang; Nurbaeti, Nurbaeti (Journal of Social Research, 2023)
Gastronomic tourism, a multifaceted concept encapsulating one's holistic experience with food and beverages, is becoming increasingly significant in the realm of travel and cultural exploration. This research embarks on a compelling journey to unravel the potential for gastronomic tourism development within the enchanting landscapes of Outer Baduy. A descriptive qualitative approach intertwined with an ethnographic paradigm forms the foundation of this investigative endeavor. The methodology employed to gather insights is centered around in-depth interviews with an array of informants encountered during an immersive sojourn in Outer Baduy. Evidently, gastronomy in this region holds untapped promise, offering a treasure trove of opportunities for further exploration. The rich tapestry of community activities in Outer Baduy is poised to serve as captivating tourist attractions. These include active engagement in the traditional practices of planting huma rice, extracting palm sap to craft delectable palm sugar, and the thrill of foraging for honey in the lush forests. Furthermore, the preservation of age-old customs and rituals, such as the solemn observance of "ngaseuk" marking the commencement of huma rice cultivation, adds a profound layer to the gastronomic journey, showcasing the enduring tapestry of culture and tradition within Outer Baduy. The findings of this study suggest that gastronomic tourism in this unique region holds immense potential, offering an authentic and enriching experience for travelers seeking to explore the intersection of food, culture, and tradition.